Mitigation and correction measures used by the state to repair the damage caused by mining companies in the El Oasis neighborhood of the municipality of Certegui, department of Chocó - Palacios Mena, Denier; Moreno Rodallega, Maryuri (DIXI, 2019)
Purpose: The investigation is aimed at determining the mitigation and correction measures used by the state to remedy the damage caused by mining companies in the El Oasis neighborhood of the municipality of Certegui, department of Chocó, taking into account the provisions of Law 99 of 1993 and of Law 70 of 1993 (Black Communities Act), article 29.Methodology: A prospective analysis is made to know in detail the effects of the mining activity in the El Oasis neighborhood. The laws that are part of this investigation are taken into account to clarify the compliance of the state in the areas that are far away from the central government and the institutional design of the municipality of Certegui.Findings: At a national level, there are serious deficiencies in facing environmental problems, materialized in the adoption of more suitable personnel. This is because universities are just beginning to train in specializations and undergraduate programs such as Agrarian Law or Land Law, and environmental education is in full academic recognition that manages and promotes public policies based on soil sustainability. At the same time, there is a lack of control of the damages produced by mining companies.Conclusions: To date, it is not known why the Constitutional Court did not express the normative support of the concept of biocultural rights. It is important to emphasize that, in the internal law, this antecedent does exist, which is an event of great importance for the ecological revolution.
Keywords: Political Constitution; law; environmental law; mining companies; social state under the rule of law